Application of Intrapartum Hypnosis in First-Stage Midwifery Care to Reduce Maternal Anxiety - Putri Belenda Ratih; Rina Nursanti; Ummi Daimah; Desy Setiawati; Jasmi Jasmi; Dian Lestari (Poltekkes Kemenkes Palembang, 2026)
Maternal anxiety during the first stage of labor is a psychological factor that can affect maternal comfort, increase pain perception, and hinder labor progress. Various non-pharmacological interventions have been developed to help reduce maternal anxiety, one of which is intrapartum hypnosis. Intrapartum hypnosis is a deep relaxation technique combined with positive affirmations to help mothers achieve a calm, relaxed, and confident state during labor. The application of intrapartum hypnosis in midwifery care is expected to reduce maternal anxiety during the first stage of labor. Objective: To determine the application of intrapartum hypnosis in midwifery care during the first stage of labor to reduce maternal anxiety. Methods: This study used a qualitative method with a case study design on mothers in the first stage of labor. Data collection was conducted through interviews and observations. Results: Before the application of hypnosis, mothers expressed feelings of anxiety and worry about the labor process. After intrapartum hypnosis, mothers appeared more relaxed, calm, and able to control their anxiety. They also showed increased confidence in the first stage of labor and were able to make positive affirmations throughout the labor process. Conclusion: The application of intrapartum hypnosis in midwifery care during the first stage of labor helps reduce maternal anxiety.